Problematika Implementasi Kurikulum 2013 PAUD di RA Masjid Al-Azhar Permata Puri Ngaliyan Semarang - Mursid Mursid (Universitas Al-Hikmah Indonesia, 2018)
This article thoroughly describes the problems of 2013 Curriculum at RA Al-Azhar Permata Puri Ngaliyan Mosque, Semarang implementation. Based on descriptive analysis, this study shows that: 1) The number of students and teachers in one class is not in accordance with the PAUD Standard guidelines. The standard for RA-B class is 15 students with 1 PAUD Professional teacher and 1 accompanying teacher, as well as RA-A class with 12 children. Reality in the field, 1 teacher center guides and accompanies 15 students. 2) Lack of teacher knowledge about the 2013 PAUD Curriculum, 3) Lack of supporting infrastructure facilities, such as performance space, center space, library space which is still one room with headmaster and staf room, 4) At least the attention of parents of students, 5) Time the transition in center learning is always not in accordance with the time written by the teacher in lesson plan (RPPH). Based on the results of this study, it is expected to be an information and input material for interested parties in implementing the 2013 PAUD Curriculum, so that quality and high-competitiveness education can be realized.